การสังเคราะห์ตัวติดตามสำหรับตรวจหาโพลีฟอสเฟตแบคทีเรียในน้ำเสีย - อุรัจฉวี อุณหเลขกะ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Using wastewater mediu, 143 bacterial isolates were obtained from water samples of the Si Phraya wastewater treatment plant. The of the isolates are polyphosphate accumulating bacteria (PAB), proving by Alkaline Loeffler’s Methylene Blue staining. Among 10 PABs, only isolates which are assigned as CUW-1, CUW-3 and CuW-8, that showed phosphate removal activity higher than 25% removal as pure cultures. By using physiological and biochemical tests, CUW-1, CUW-3 and CUW-8 identified as Propionibacterium sp., Corynebacterium sp. and Renibacterium sp., respectively. Specific activity of polyphosphate kinase in aerobic condition of each strain was 0.3945, 0.552 and 0.256 unit/mg protein, respectively. Two synthetic oligonucleotide primers were designed using available amino acid sequence information on the most conserved region of the PPK proteins from many bacteria and were successfully in amplifying 650 basepairs fragment of the ppk gene from e. coli JM109 but no amplified products of the 3 selected strains were detected. The EcoRI digested genomic DNA from the 3 strains were hybridized with the PCR product from E. coli JM109 which digoxigenin labeling. Hybridization signal of CUW-1 and CUW-3 were detected at 3 kilobases whereas E. coli JM109 labeling with a positive control had signal around 10 kilobases.